Dinomania! : an epic battle of dinosaur facts - Baines, Rebecca (Factmania : epic battle of facts, 2024)
"It's an epic battle of info in Factmania, a new series that showcases a heap of fun facts in a thrilling format! Which dinosaurs would win the gold medal in a Dinosaur Olympics? In a speed race, which dinos would take the top prizes? Filled with factual knowledge and brimming with excitement for kids ages 7-10, Dinomania delivers pages of T-Rex-sized information that's cool to read, will help with homework, and answers all you need to know through dino-versus-dino page designs."--Amazon.com